Public opinion - Glynn, Carroll J.; Herbst, Susan; Lindeman, Mark; J. O'Keefe, Garrett (Boulder, CO : Westview Press, 2015)
'Public Opinion is a comprehensive and multidisciplinary examination of public opinion in the United States. Drawing on scholarship in political science, psychology, sociology, and communications, the authors explore the nature of political and social attitudes in the United States and how these attitudes are shaped by various institutions, with an emphasis on mass media. The book also serves as a provocative starting point for the discussion of citizen moods, political participation, and voting behavior. Feature boxes and illustrations throughout help students understand all aspects of the elusive phenomenon we call public opinion. The third edition has been thoroughly revised and updated to reflect how public opinion is studied today, and to incorporate current data and debates. The book now contains two revised and reframed theory chapters--'Group Membership and Public Opinion' and'Public Opinion and Social Process'--as well as new coverage of the influence of online and social media on public opinion, especially in issue opinions and campaigns'--
Machine generated contents note: Preface -- Part One: Introducing Public Opinion -- 1. The Meanings of Public Opinion -- 2. The History of Public Opinion -- 3. Methods for Studying Public Opinion -- Part Two: Theories of Public Opinion -- 4. Public Opinion and Democratic Theory -- 5. Psychological Perspectives on Public Opinion -- 6. Stereotyping, Social Norms, and Public Opinion -- 7. Perception and Opinion Formation -- 8. Economic Approaches -- Part Three: Public Opinion in Context -- 9. Content and Conflict in Public Opinion -- 10. Public Opinion and Policymaking -- 11. Communicating, Campaigning and the Public (TK) -- 12. Looking Ahead.
Includes bibliographical references and index.
Keywords: Public opinion -- United States; Public opinion -- Political aspects -- United States